IMPLEMENTASI EKONOMI SYARIA'H : MARKETING SYARI'AH: UNSUR NAJASYI DALAM MODUS BUZZER MARKETING - Solekhan, Ahmad (IKHTIYAR JURNAL EKONOMI SYARI'AH, 2025)
Buzzers in digital promotional media do have a lot of positive sides forbusiness actors, but in practice sometimes in carrying out their duties they tend to have the potential to be dishonest and not objective, such as the dissemination of inappropriate information, slander to more towards elements of fraud. There are several negative actions of buzzers on social media that are easy to find, such as false reviews of a product. Buzzers are also considered detrimental to consumers because buzzers, in conveying information, tend to provide information that does not match reality, by creating fake accounts to help increase ratings and restore a good image to the company.good image of the company. This buzzer practice causes disappointment and losses to consumers who rely on reviews and ratings to make purchasing decisions, and this can even be included in the spread of hoax information. One form of hoax information practiced by marketing buzzers is najshi (نجشى).They do this because the compensation earned by buzzers is often based on the quantity of products that the public responds to or even sells.This research will examine the taklifi law of buzzer marketing and the principles that must be fulfilled, so that it does not conflict with shar'i values.)